Correlation of Electromyography and Magnetic Resonance Imaging Findings in the Diagnosis of Suspected Radiculopathy - Yıldız Arslan; Ebru Yaşar; Yaşar Zorlu (Türk Nöroloji Dergisi, 2016)
INTRODUCTION: Patients with pain or numbness without motor deficits are the most common group referred to electrophysiology laboratories as suspected radiculopathy. We wanted to investigate whether electromyography (EMG) was useful for this group in the diagnosis or therapy of radiculopathy. Our aim was to investigate the correlation and classification of EMG and magnetic resonance imaging (MRI) findings in the diagnosis of suspected radiculopathy. METHODS: We included 74 patients with a ≥2-month history of numbness and pain in the neck and back that radiated into the arm or leg. Patients with diabetes mellitus, previous disc or spine operation, polyneuropathy, spinal cord diseases (tumor, infection or syrinxs), motor deficits, and abnormal nerve conduction studies were excluded. RESULTS: The mean age of the patients was 51.58±11.53 years. In total, 41 (55.4%) patients were women and 33 (44.6%) were men; 48.8% (n=36) showed cervical radiculopathy and 51.2% (n=38) exhibited lumbosacral radiculopathy. The most common MRI finding was protrusion (37.8%), and the most common EMG finding was re-innervation (59.5%). The correlation of MRI and EMG findings was significant in lumbar radiculopathy (p=0.007), but not in the cervical radiculopathy results (p=0.976). DISCUSSION AND CONCLUSION: EMG and MRI findings were compatible for lumbar radiculopathy, but not for cervical radiculopathy in mild to moderate grades.